PENGARUH LOCUS OF CONTROL, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, KECERDASAN INTELEKTUAL TERHADAP PERILAKU ETIS MAHASISWA AKUNTANSI DI UNIVERSITAS SLAMET RIYADI SURAKARTA - Putri Anggreini Pramudita; Aris Eddy Sarwono (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to examine the effect of Locus of Control, Emotional Intelligence, Spiritual Intelligence and Intellectual Intelligence on the ethical behavior of accounting students partially or simultaneously. The population in this study were Active Students of the Accounting Study Program Semester 6 and 8 of the Faculty of Economics, Slamet Riyadi University, Surakarta. The sample in this study amounted to 34 obtained from 193 Active Students of the Accounting Study Program in semesters 6 and 8 using the random sampling method. The data analysis technique used in this study is multiple linear regression analysis using SPSS software. The results of this study indicate that Locus of Control, Emotional Intelligence has a negative and insignificant effect on the ethical behavior of Accounting students. While Spiritual Intelligence, intellectual intelligence has a positive and insignificant effect on the ethical behavior of accounting students.